An Overview of Targeted Drug Delivery Systems - Stanekzai, Azimullah (Journal of Natural Sciences – Kabul University, 2020)
A targeted drug delivery system is a special form of drug delivery where the medicament is selectively targeted or delivered only to its site of action or absorption, avoiding non-target organs, tissues, or cells. This system seeks to concentrate the medication in the tissues of interest while reducing its concentration in remaining tissues, thus improving efficacy and reducing side effects. Two strategies are widely used for drug targeting: passive targeting and active targeting. Nanoparticles are very small, and nano drug delivery allows for the delivery of drugs that have poor solubility in water, while also helping to avoid first-pass metabolism in the liver. In this system, the drug can remain in the bloodstream for a longer time, leading to fewer fluctuations in plasma levels and minimal side effects.